Answer:
Step-by-step explanation:
Given expression is,
(2x - 1)² + 2(2x - 1) = (2x - 1)(2x + 1)
To prove this identity we will take the left hand side of the equation and will prove equal to the right side.
(2x - 1)² + 2(2x - 1) = (2x - 1)(2x + 1)
4x² - 4x + 1 + 4x - 2 = (2x - 1)(2x + 1)
4x² - 1 = (2x - 1)(2x + 1)
(2x - 1)(2x + 1) = (2x - 1)(2x + 1) [Since a² - b² = (a - b)(a + b)]
Answer:
X=10
Step-by-step explanation:
3x=30
3(10)=30
30=30
30+42=72
I hope this helps!
Answer:
Step-by-step explanation:
<em>Note all arguments of trigonometric functions are in degrees.</em>
<em />
Since tan(35)=4/(longer dotted leg of the triangle), the length of this longer dotted leg is thus 4/tan(35).
Since A=bh, the area is (4/tan35)(12), and you can just plug this into a calculator.
R-9s=2 add 9s to both sides
r=2+9s making 3r-3s=-10 become:
3(2+9s)-3s=-10 perform indicated multiplication on left side
6+27s-3s=-10 combine like terms on left side
6+24s=-10 subtract 6 from both sides
24s=-16 divide both sides by 24
s=-16/24
s=-2/3, making r-9s=2 become:
r-9(-2/3)=2 perform indicated multiplication on left side
r+6=2 subtract 6 from both sides
r=-4
So s= -2/3 and r= -4